The valley of fear: A Sherlock Holmes adventure Collins Classics - Doyle, Arthur Conan (London : Harper Collins Publishers, 2016)
In this final Sherlock Holmes novel, the great detective is drawn into a complex case involving a gruesome murder at a secluded English manor. Using his sharp deductive skills, Holmes uncovers connections between the killing and a secretive criminal organization in America. Blending classic detective work with a dramatic backstory, the novel weaves together mystery, danger, and Holmes$1 (Bs ongoing battle with his nemesis, Professor Moriarty.s
Keywords: English - Fiction Book